APLIKASI E-COMMERCE UNTUK MENINGKATKAN USER EXPERIENCE PADA PT. JAYA UTAMA BEARING - Jacky Setiawan; Ayouvi Poerna Wardhanie; Endra Rahmawati (LPPM Universitas Abdurrab, 2023)
One of the keys to success in building e-commerce that can provide convenience and comfort for its users is knowing the users' needs. This study aims to create a website-based online store application that can improve user experience, especially for Jaya Utama Bearing companies engaged in selling industrial goods and auto spare parts so that they have detailed with clear product information, consumers can easily make transactions online, have an attractive visual design, and makes it easier for companies to manage and store sales reports. Based on the results of interviews with 30 customers using the User Experience Questionnaire, it was found that on the previous website, for the factors of attractiveness, clarity, efficiency, accuracy, stimulation and novelty, the results were below average and even bad, causing a decrease in income due to lost consumer loyalty. The results of this study are a catalog feature that can be filtered by category to display detailed product information, product purchase features, chat features to accommodate customer questions before buying, review or feedback features after a purchase transaction, and a sales report recording feature. The researcher also compared websites before and after using UEQ with the same 30 respondents, where it was seen that the scores for the six factors had increased from below average to above average and bad to good.